Parathyroid adenoma with rare severe pathological osteolytic lesion: a case report and literature review - Chen, Jia; Tang, Gusheng; Peng, Ye; Cheng, Hui (Frontiers in Oncology, 2023)
Parathyroid adenomas are benign proliferative disorders of the parathyroid gland. Due to elevated levels of parathyroid hormone (PTH), patients typically exhibit hyperparathyroidism and elevated serum calcium levels. We report this newly diagnosed case, with rare pathological osteolytic lesions. The radiological evaluation showed multiple bony lesions in multiple parts of the pelvis, vertebral body and spinous process, suggesting hematological neoplasms or bone marrow metastatic carcinoma. Morphology revealed a large number of abnormal cells on bone marrow smear. Furthermore, serum calcium and PTH were significantly increased compared to normal levels. Doppler color ultrasound showed thyroid mass (left), suspected parathyroid adenoma, thyroid and isthmus nodular goiter (right). This patient was performed a bilateral neck exploration with parathyroidectomy, and serum calcium and PTH are significantly decreased on second day after operation, and had surgical cure.